The Interior palimpsests of the French Book Illustration of the 18th Century: The Problem of Recognition - Borshch, Elena V. (Actual Problems of Theory and History of Art, 2018)
The French illustrators of the 18th century created the convincing and exact portrait of the interior of the epoch. They preferred the exact and detailed method of the interior depiction, which proves the use of visual sources. The article is devoted to the problem of the recognition of analogues of interior background in the book illustration of the 18th century. By the comparative analysis of the illustrations to one literary text, an attempt to establish image primary sources has been made. For the designation of visual layers of an image, the term palimpsest has been used. The theme has been dealt with on the example of the illustrations of Charles Eisen to Tales and short stories in verses by Jean de La Fontaine (1762). The interior’s illustrations of Charles Eisen were compared with design engravings of the second half of the 17th — the first half of the 18th centuries. Simultaneously, the illustrations by Charles Eisen were compared with the illustrations by Romain de Hooge (1685), the illustrations from Suite Larmessin (1730) with the illustrations by Charles-Nicolas Cochin-younger (1743). As a result, we draw the conclusion that there were several palimpsests of the image of the interior in the works of Charles Eisen. Among them, there are the projects of the interiors of “Louis XIV style”, the projects of the interiors “Louis XV style”, the earlier suites of illustrations to the same text; literary illustrations to other texts. The reference during the 1750s to the heritage of the architects of the second half of the 17th century confirms the coherence of this stage to the formation of French Neoclassicism. The comparative analysis of design engravings and book engravings as well as the comparison of the different suites of illustrations offer the chance to reconstruct the artistic methods of the 18th century.